Assessment of quality of care provided to patients who died in the care of Tshwane District Hospital - Zele-Mqonci, Nozuko (Department of Medicine, 2019)
Objective: To assess the quality of care rendered to admitted patients in need of end-of- life care at Tshwane District Hospital in Pretoria Central, Gauteng, South Africa. Method: A combined retrospective review of the patient’s folder and a descriptive qualitative study through interviewing the deceased patient’s relatives was used. An after-death audit (ADA) tool, developed by the researcher and supervisor using the Gold Standard Framework ADA Tool, which is used in the UK was used as a reference as was agreed to be appropriate for this study. This explored the ability of healthcare workers at district hospital level to identify patients who were at end-of-life through noting and recording the end-of-life symptoms and signs and the interventions taken within the last 72 hours of the patients’ life. An interview guide for the bereaved family members was developed using the family medicine principle of patient-centred care and management in order to investigate their perception of the quality of care rendered to their relatives whilst admitted at Tshwane District Hospital during their last days. Results: 96 files were audited, revealing that patients between the ages of 21 years to 101 years were admitted. This confirmed the increase in number of older people with incurable chronic disease and multi-morbidity such as malignancy and HIV/AIDS, as compared to younger patients. Of those admitted, 55.2% were admitted from home and 15.6% were referred from a tertiary institution. 83% of these patients were admitted due to non-cancer diagnosis, of which about 36% of those admissions were HIV- related, followed by renal causes (10%), cardiac (10%) and COPD (3%). Cancer accounted for approximately 16.6% of the admissions. The duration of stay was between 4.3 to 4.7 days, with younger and white patients admitted for shorter periods compared to their older and black counterparts. The audited patient records recorded signs in their files (gasping - 51.04%, low BP, low pulse - 18.75%) and symptoms of end-of-life (confused, ill, weak - 18.75%) but patients were not identified or recognised as being close to end-of-life and were not referred for palliative care. The only recorded intervention that patients received was oxygen by mask (54.1%). Record reviews and family interviews revealed poor patient involvement in decision-making as only about 9.3% were involved in their own care management. There was also a lack of family involvement in patient management (4.4%), poor multi-disciplinary /team involvement as only 29.2% were referred to the other members of the multi-disciplinary team, and a low referral to hospice (8.3%). According to the 18 consented family members’ interviews conducted, there was lack of information with poor updates on patients’ problems or prognosis. Only 58,8% felt that enough information was given and the members interviewed were not offered any additional services (76.5%). They indicated that they thought referral to hospice would have improved the quality of life and care of their loved ones at end-of-life. The majority of family members (88.24%) also reported little care for patients during the dying phase as their relatives (patients) had symptoms (23.53%) but nothing had been done to relieve these symptoms. Conclusion: There is an increased need for palliative care and end-of-life care education and skills at district hospitals as most patients are admitted or down-referred for care to district hospitals at the end-of-life. When looking at interventions rendered, the study revealed poor quality of care rendered to patients at their end-of-life, poor patient and family involvement in management decisions, and a lack of multi-disciplinary approach of care. Helping or training of the healthcare workers at District Care level Hospitals to be able to recognise a patient in need of palliative care or have an ability in recognising those patients who require end-of-life care or are in their last 72hrs of life (which refers to the patients in the final hours or days of their lives, or those with a terminal illness that has become progressively advanced) is still a challenge in the District level hospital. The integration of palliative care at district hospitals would improve the quality of care for both patients and their families.